NORMALIZACJA SYTUACJI PRAWNEJ ZWIĄZKÓW WYZNANIOWYCH W FEDERACJI ROSYJSKIEJ W OPARCIU O USTAWĘ RRFSR O WOLNOŚCI WYZNAŃ Z 25 PAŹDZIERNIKA 1990 ROKU - Byś, Jelena (Prawo Kanoniczne, 2004)
In the USSR in the 80s of the 20lh century perestrojka led to great changes in every field of public life but especially modifications were introduced in religious sphere. An ultimate need of reform of the legislation in the RSFSR and later in the Russian Federation concerning freedom of conscience and religion put many problems before legislative organs after seventy years of total negation of God and religion. In the first place the article concentrates on the reasons of adoption of the RSFSR O N FREEDOM OF R ELIG IO N of October 25, 1990 and further on the norms it contains. An important achievement of the law’s authors consists in taking into consideration religious freedom in individual and community dimensions. Of great importance are guarantees of individual freedom of religion mainly as a manifestation of respect for every citizen of any belief and religion and the right to religious beliefs. The principles defining relations of religious associations to state and in particular the principle of equality of religious associations in the face of state imply a secular type of state and is its characteristic feature. It is shown also how various tendencies clash in the religious policy of Russia. Generally they may be reduced to two main trends: liberal and conservative. Liberal tendency found its manifestation in adoption in 1990 of new legislative acts greatly influenced by the patterns existing in the democratic Western countries of secular type. However, conservatism became apparent in some restrictions of religious freedom and in legislative tendencies implying religious type of the state with Orthodox Church as a national religion. The new Constitution of the Russian Federation adopted in 1993 approved new legislative acts included in the law. Evolution of religious legislation in the Russian Federation is not completed yet, it is in the process of development but only future will show what direction it will take.